A190 SEROPREVALENCE OF HEPATITIS B VIRUS IN ASIAN CANADIANS WHO ARE UNAWARE OF THEIR HBV STATUS IN GREATER VANACOUVER. (15th March 2019) - Lee, J G; Yoshida, E M; Ho, F; Lowe, C; Sum, V; Kwan, P
Abstract: Background: The seroprevalence of hepatitis B virus (HBV) is 0.4% in Canada, but varying rates has been reported in different populations. Up to 40% of HBV carriers have no knowledge of their diagnosis, which highlights the need to identify and manage these patients who are at risk of significant morbidity and mortality via chronic hepatitis and its complications. In 2015, a small pilot study conducted in the Lower Mainland showed a higher-than-expected rates of active hepatitis B in Asians, but larger scale studies were needed to validate their findings. Aims: To determine the seroprevalence of HBV among attendees of Asian health events who had no prior knowledge of their hepatitis B status in Greater Vancouver, British Columbia. Methods: Attendees at Asian health events hosted by the Canadian Liver Foundation who had no knowledge of their hepatitis B status were invited to participate in the study on a voluntary basis. They provided answers to a questionnaire including age, ethnicity, years lived in Canada, and other medical history. Blood was then drawn for HBV serologies with their consent. Active HBV was defined as HBV surface antigen (HBsAg) positive. Only those with correct demographic information matched to serological results were included in the study. Comparisons among response groups were calculated using Fisher's exact test; P<0.05 was considered to be statistically significant. Results: There were 2210 consenting attendees of the fairs, of whom 2202 were included in the study. The median age was 65 years. The majority of participants (76%) were Chinese. These participants had resided in Canada for an average of 28.3 years. Active HBV infection was found in 39 participants (1.8% [95% CI 1.5% to 2.1%]). Almost all of the participants (97.0%) had a family physician. No significant differences were found between the HBV carriers vs. non-HBV carriers, including age, number of years resided in Canada, or place of birth. Conclusions: The seroprevalence of HBV in Asian Canadians living in Greater Vancouver who had no prior knowledge of their HBV status was 1.8%–higher than nationally reported rates. Our results highlight that the lack of awareness of HBV infection remains a significant clinical issue in the Asian community of Greater Vancouver. Funding Agencies: Canadian Liver Foundation